Apropriação dos gêneros carta aberta e petição on-line construídos por alunos do 9° ano do ensino fundamental na produção de textos do campo da vida pública - Benício, Flávia Maria Araújo (2024)
The objective of the present research was the appropriation of the online petition and open letter genres by middle school students (9th grade) through the production of texts in the field of public life, aiming at the practice of critical citizenship. For this purpose, a didactic device was developed to enhance students' use of argumentative strategies in the construction of reivindicative and propositional texts. The theoretical basis adopted was Socio-Discursive Interactionism, which advocates the centrality of language in and for human interactions and these interactions for human development. This theory proposes a method of text analysis, from which we emphasize, without detriment to a holistic view, the dimensions of the production context, textual infrastructure (especially the argumentative sequence), and enunciative mechanisms. We worked on these elements through text production proposals that took into account problems related to the students' social context, seeking to make them feel the need to write and, thus, understand the social role of writing in civic life. In addition to Socio-Discursive Interactionism (SDI), we relied on Adam's (2019) concepts on the argumentative sequence, comparing them with how Bronckart (2023), a pioneer of SDI, addresses this topic. Regarding argumentation, we used concepts from Perelman and Olbrechts-Tyteca (2014) and Amossy (2020), as they offer a comprehensive perspective on argumentation theory and rhetorical practice, providing conceptual and analytical tools to understand and use arguments effectively and persuasively. The research is characterized as action research, and we applied two didactic sequences (Dolz and Schneuwly, 2004), one on the online petition genre and the other on the open letter. Each didactic sequence was driven by themes that directly affected the students, such as the school's structure and bullying practices. At each stage of implementing the didactic sequences, we observed the students' challenges with writing after two years of fully remote education, but also the progress between the initial and final productions: better mastery of the addressed genres, identifiable production context, organization between the author's voice and social voice, among others.